Effects of norepinephrine on microglial neuroinflammation and neuropathic pain. Issue 4 (8th December 2021) - Zou, He‐Lin; Li, Juan; Zhou, Jun‐Li; Yi, Xi; Cao, Song
Abstract: Norepinephrine (NE) is an important neurotransmitter in the central nervous system. NE is released from locus coeruleus neurons and is involved in a variety of physiological and pathological processes. Neuroinflammation is a common manifestation of many kinds of neurological diseases. The activation of microglia directly affects the status of neuroinflammation. Several kinds of adrenergic receptors, which anchor on microglia and can be regulated by NE, affect the activation of microglia and neuroinflammation. NE influences chronic pain, anxiety, and depression by regulating the activation of microglia. Abstract : 1. Abnormally activated microglia release inflammatory mediators and cause neuroinflammation. 2. Persistent neuroinflammation may cause anxiety/depression. 3. Neuropathic pain and neuroinflammation affect each other to form a vicious circle. 4. Norepinephrine released from the locus coeruleus inhibits abnormal microglial activation and relieves chronic pain.